Green Warbler Phylloscopus (trochiloides) nitidus recorded at Ottenby, Öland: a first record for Scandinavia - Irwin, Darren E; Hellström, Magnus (Ornis Svecica, 2007)
This paper presents the circumstances surrounding the findings and identification of the first Green Warbler Phylloscopus (trochiloides) nitidus for Sweden. The bird was caught and ringed at Ottenby Bird Observatory on May 29, 2003, but was not formally identified to subspecific level until after a DNA analysis of the collected blood-sample was conducted. This constitutes the sixth European record outside the restricted breeding area.